2006
DOI: 10.1007/s10529-006-9201-9
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of the anti-apoptotic baculovirus p35 gene in passion fruit induces herbicide tolerance, reduced bacterial lesions, but does not inhibits passion fruit woodiness disease progress induced by cowpea aphid-borne mosaic virus (CABMV)

Abstract: The introduction of anti-apoptotic genes into plants leads to resistance to environmental stress and broad-spectrum disease resistance. The anti-apoptotic gene (p35) from a baculovirus was introduced into the genome of passion fruit plants by biobalistics. Eleven regenerated plants showed the presence of the p35 gene by PCR and/or dot blot hybridization. Transcriptional analysis of regenerated plants showed the presence of specific p35 transcripts in 9 of them. Regenerated plants containing the p35 gene were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 14 publications
0
20
0
2
Order By: Relevance
“…With regard to diseases such as passion fruit woodiness (PWD) (caused in Brazil by Cowpea aphid-borne mosaic virus ) and the bacterial spot disease (caused by Xanthomonas axonopodis pv. passiflorae ), for the which chemical control measures are not effective and resistant cultivars are not available, a growing number of advances in the use of genetic engineering have been observed in recent decades [105,106,107,108]. …”
Section: Contributions Of Molecular and Genetic Studies For The Chmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to diseases such as passion fruit woodiness (PWD) (caused in Brazil by Cowpea aphid-borne mosaic virus ) and the bacterial spot disease (caused by Xanthomonas axonopodis pv. passiflorae ), for the which chemical control measures are not effective and resistant cultivars are not available, a growing number of advances in the use of genetic engineering have been observed in recent decades [105,106,107,108]. …”
Section: Contributions Of Molecular and Genetic Studies For The Chmentioning
confidence: 99%
“…Although in smaller proportions or in less advanced stages, studies devoted to obtaining transgenic plants were also conducted with P. edulis for resistance to diseases and herbicides through the introduction of a baculovirus anti-apoptotic gene ( p35 gene) [108] and the resistance to bacterial spot disease by introducing the sequence of the attacin A gene ( att A) [110]. Plants of P. edulis transformed with p35 gene sequences showed no resistance to CABMV but showed increased tolerance to bacterial spot disease and glufosinate herbicide when compared to non-transgenic plants [108].…”
Section: Contributions Of Molecular and Genetic Studies For The Chmentioning
confidence: 99%
See 1 more Smart Citation
“…Many viruses contain the antiapoptotic genes to block the defense-by-death response of host cells (Wang et al 2004). The expression of antiapoptotic genes such as iap and p35 from baculoviruses, ced-9 from Caenorhabditis elegans and bcl-2 from humans in tobacco, tomato, and passion fruit plant (Passiflora spp) suppressed the extensive cell death caused by fungal and bacterial pathogens and also enhanced resistance to some abiotic stresses such as wounding, salt, cold, UV, and herbicides (Dickman et al 2001;Lincoln et al 2002;Chen and Dickman 2004;Li and Dickman 2004;Xu et al 2004;Freitas et al 2007). Particularly, baculovirus p35 and iap genes were expressed in corn embryos and embryogenic calli and their expression reduced tissue browning 3 d after cocultivation with A. tumefaciens (Hansen 2000).…”
Section: Programmed Cell Death Associated With Ros In Plantmentioning
confidence: 99%
“…p35 transgenic tobacco plants showed partial inhibition of hypersensitive response cell death compared with wild-type plants after pathogen challenge, while expression of mutant versions of the P35 protein did not show this phenotype (del Pozo and Lam 2003). In a recent study, p35 gene expression in passion fruit showed no resistance to a plant virus, but showed resistance to a bacterium (de Freitas et al 2007). However, p35 gene over-expression in plants on abiotic stress has not been documented.…”
Section: Introductionmentioning
confidence: 98%